2006
DOI: 10.1002/pd.1345
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of fetal nasal bone in a low-risk population at 11–13 + 6 gestational weeks

Abstract: In a low-risk population, the evaluation of the presence/absence of nasal bone in DS screening during the first trimester has a low sensitivity. First-trimester assessment of the nasal bone in population screening may play a lesser role than in the re-evaluation of high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…However, this figure is consistent with recent publications reporting a lower prevalence in unselected populations [9,16] . Similar findings were reported in the FASTER study, where none of the trisomy 21 fetuses showed the absence of nasal bone; however, this study is criticized based on the nasal bone evaluation technique used [13] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, this figure is consistent with recent publications reporting a lower prevalence in unselected populations [9,16] . Similar findings were reported in the FASTER study, where none of the trisomy 21 fetuses showed the absence of nasal bone; however, this study is criticized based on the nasal bone evaluation technique used [13] .…”
Section: Discussionsupporting
confidence: 82%
“…The nasal bone was found to be absent in 33% (3/9) of fetuses with trisomy 21 in our study, which is lower than in the initial reports which usually reported around 70% [1,5,6,9,14,18,19] . However, this figure is consistent with recent publications reporting a lower prevalence in unselected populations [9,16] .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Initially, sonographic assessment of the NB was thought to be a useful marker for screening for trisomy 21 in the first trimester. Inconsistent findings in subsequent studies, however, have diminished its value [40]. Sepulveda et al [41] used first-trimester nuchal translucency and NB assessment over a three-year period in 1,287 consecutive singleton cases in a recent study.…”
Section: Nasal Bone (Nb)mentioning
confidence: 98%
“…It has been reported that about 65% of Down syndrome fetuses have absent or short NB in fetal NB screening at the first and second trimesters [4]. Only 1~2% of normal karyotype fetuses have been observed [5][6][7]. Down syndrome and absent or hypoplastic fetal NB show similar evidence of high sensitivity, high specificity, and low false-positive rate for Down syndrome screening by fetal NB examination [8][9][10][11].…”
Section: Introductionmentioning
confidence: 78%